2016
DOI: 10.1353/cpr.2016.0067
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Based Participatory Research Guided Model for the Dissemination of Evidence-Based Interventions

Abstract: Background Dissemination is a principle within community-based participatory research (CBPR); however, published research focuses on the dissemination of findings from CBPR projects but less on dissemination of interventions developed through CBPR approaches. To disseminate an evidence-based lifestyle intervention tailored for Native Hawaiians and Pacific Islanders, the PILI 'Ohana Project (POP), an 11-year CBPR initiative, developed an innovative dissemination model. Objectives The Community-to-Community Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Therefore, HCFW and communities should implement strategies involving the participation of workers in discussions on occupational health in order to increase critical consciousness. In the meantime, this investigation was different from other studies in that it demonstrated that community capacity influenced critical consciousness [18]. Sheri et al [32] found that community capacity and critical consciousness, among others, are prerequisites for empowerment.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Therefore, HCFW and communities should implement strategies involving the participation of workers in discussions on occupational health in order to increase critical consciousness. In the meantime, this investigation was different from other studies in that it demonstrated that community capacity influenced critical consciousness [18]. Sheri et al [32] found that community capacity and critical consciousness, among others, are prerequisites for empowerment.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, past research has similarly shown that issue selection is more than member participation [16], and different organizational systems display different levels of issue selection [17]. Previous studies have shown that community capacity has a significant impact on critical consciousness [18] and critical consciousness has a significant impact on participation in health initiatives [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Community-based organizations.-The involvement of community leaders through community-based organizations was discussed in 80% of the articles. [62][63][64][65][66][67]69,70,[98][99][100][101][102][103][104][105][106][107][108][109][110][111][112]116,117,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136] The involvement of community-based organizations was cited as a way to leverage, build, and sustain leadership within the Pacific Islander community. 81 Community-based organizations (e.g., federally qualified community health centers and grassroots non-profit community-based organizations) were described as playing a direct role in the research design, study conduct, and dissemination of the results back to the community.…”
Section: Engaging Community Leadersmentioning
confidence: 99%
“…Community advisory board.-More than half (54%) of the reviewed articles mentioned partnering with a community advisory board. 62,[64][65][66][67]69,70,[72][73][74][75][76][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112]116,117,[120][121][122][123]…”
Section: Engaging Community Leadersmentioning
confidence: 99%
See 1 more Smart Citation